Decreasing death rates and causes of death in Icelandic children-A longitudinal analysis. - Marina Ros Levy (Public Library of Science (PLoS), 2021)
Background Global death rate in children has been declining during the last decades worldwide, especially in high income countries. This has been attributed to several factors, including improved prenatal and perinatal care, immunisations, infection management as well as progress in diagnosis and treatment of most diseases. However, there is certainly room for further progress. The aim of the current study was to describe the changes in death rates and causes of death in Iceland, a high-income country during almost half a century. Methods The Causes of Death Register at The Directorate of Health was used to identify all children under the age of 18 years in Iceland that died during the study period from January 1st, 1971 until December 31st, 2018. Using Icelandic national identification numbers, individuals could be identified for further information. Hospital records, laboratory results and post-mortem diagnosis could be accessed if cause of death was unclear. Findings Results showed a distinct decrease in death rates in children during the study period that was continuous over the whole period. This was established for almost all causes of death and in all age groups. This reduction was primarily attributed to a decrease in fatal accidents and fewer deaths due to infections, perinatal or congenital disease as well as malignancies, the reduction in death rates from other causes was less distinct. Childhood suicide rates remained constant. Interpretation Our results are encouraging for further prevention of childhood deaths. In addition, our results emphasise the need to improve measures to detect and treat mental and behavioural disorders leading to childhood suicide.